Critical analysis of Mat as an iconic character and its cultural manifestation in Lat The Kampung Boy animation / Juhanita Jiman - Jiman, Juhanita (Institute of Graduate Studies, UiTM, 2017)
This thesis critically studies Mat as an iconic animation Malaysian character and how much the visual values (line and colour) being exploited to establish its appearance. Mat from Lat the Kampung Boy is chosen to be the subject of this study because of his presence and effectiveness in his genre is well established. Because of visual appeal is very important in creating a believable, strong and effective iconic character, this study is about finding and determining what and how far visual elements can be exploited to make a true iconic character. The visual investigations in this thesis include: elements of design (line and colour) and Principles of Animation (visual appeal and solid drawing). On top of from visual elements, there are two other major influences affecting the development of iconic characters; local and imported elements. These two influences are going to be studied and addressed thoroughly as well. This thesis employed a thorough analysis and qualitative methods to seek tangible data and information that will help the visual establishment of iconic character in Malaysian animation industry.